PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) MENUJU ENTREPRENEUR VILLAGE DI DESA KEDUNGWEDORO, TURI, LAMONGAN PADA PASAR GLOBAL - Siska Ayu Wulandari; Ahmad Aldi Ardiansyah; Khusnul Khotimah (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2023)
Micro, Small and Medium Enterprises (MSMEs) have proven to contribute to the Indonesian economy. MSMEs have an important role in national development, namely employment, income distribution, rural economic development, increasing non-oil and gas exports, and increasing Gross Domestic Product (GDP). The reality of MSME development is still very difficult to implement, especially in rural areas. Residents with limited knowledge, living in small business activities in the traditional sector, limited infrastructure and government access are one of the factors inhibiting economic development and growth in Indonesia. Therefore, the entrepreneurial village (Entrepreneurs Village) through the development of Micro, Small and Medium Enterprises (MSMEs) exists as a solution to an effective economic system that makes it easier for people to be ready to compete in the global market. With the aim of expanding employment opportunities, equal distribution of income, alleviating poverty, creating entrepreneurial villages (Entrepreneurs Village) so as to encourage policies to improve infrastructure, technology, capital, and MSME institutions. This community service activity aims to provide socialization to MSMEs in Karangwedoro Village, Turi, Lamongan so that the businesses being run are able to survive and compete in the global market and grow even better by paying attention to the product, place, promotion and price of the products offered. This community service activity is carried out using the class method as the delivery of material given to MSMEs, direct coaching methods to get different coaching, because the problems faced by each MSME vary and also use direct practice methods so that MSME actors can do it independently. . The results of this community service activity include: 1) MSMEs know the strategy for developing a product, especially through product packaging design, 2) MSMEs know sales tips and tricks through social media, 3) MSMEs learn to create social media accounts as a means of product promotion via Instagram and Bukalapak online sales account, and 4) MSMEs are able to make structured bookkeeping.